DEVELOPMENT OF MEASURES TO IMPROVE THE EFFICIENCY OF IRRIGATION TECHNOLOGY FOR GRAIN FIELDS ON FARMS IN THE BUKHARA REGION - Avliyokulov , Mukhammad M; Eshmanov , Khusniddin N (Educational Research in Universal Sciences, 2024)
In this article, when increasing the efficiency of sprinkler irrigation systems in agricultural fields, the method of grain irrigation, water-physical properties of the soil, salt regime, changes in the level and mineralization of groundwater, grain growth, development, productivity and various methods for determining water consumption of grain, soil salinity, primary and secondary salinization, natural and artificial factors causing salinity to obtain high yields in agriculture.